Evaluation of simple hand-held Mechanical systems for harvesting tea (Camellia Sinensis) - Burgess, Paul J.; Carr, M. K. V.; Mizambwa, F. C. S.; Nixon, D. J.; Lugusi, J.; Kimambo, E. I. (Cambridge University Press, 2006)
Over an eight-year period, harvesting methods based on simple mechanical aids (blade and shear) were evaluated against hand harvesting on mature morphologically contrasting tea clones in Southern Tanzania. The effects of shear step height (5-32 mm) and the harvest interval (1.8-4.2 phyllochrons) were also examined. Except in the year following pruning, large annual yields (5.7- 7.9 t dry tea ha[minus sign]1) were obtained by hand harvesting at intervals of two phyllochrons. For clones K35 (large shoots) and T207 (small shoots), the mean harvested shoot weights were equivalent to three unfurled leaves and a terminal bud. The proportions of broken shoots (40-48 %) and coarse material (4- 6 %) were both relatively high. Using a blade resulted in similar yields to hand harvesting from K35 but larger yields from T207 (+13 %). The yield increase from clone T207 was associated with the harvest of more shoots and heavier shoots, smaller increases in canopy height, and a higher proportion (7-9 %) of coarse material compared to hand harvesting. On bushes, which had been harvested by hand for two years following pruning, using flat shears (no step) supported on the tea canopy resulted, over a three year period, in yields 8-14 % less than those obtained by hand harvesting and, for clone K35, a reduction in the leaf area index to below 5. The development of a larger leaf area index is made possible by adding a step to the shear. However, since annual yields were reduced by 40-50 kg ha[minus sign]1 per mm increase in step height, the step should be the minimum necessary to maintain long-term bush productivity. As mean shoot weights following shear harvesting were about 13 % below those obtained by hand harvesting, there is scope, when using shears, to extend the harvest interval from 2 to 2.5 phyllochrons.